A safe, stable, and convenient three-dimensional device for high Le Fort I osteotomy - Keisuke Sugahara (Maxillofacial Plastic and Reconstructive Surgery, 2020)
Abstract Background Le Fort I osteotomy is a highly effective treatment for skeletal jaw deformities and is commonly performed. High Le Fort I osteotomy is a modified surgical procedure performed for improving the depression of the cheeks by setting the osteotomy higher than the conventional Le Fort I osteotomy. Developments in three-dimensional (3D) technology have popularized the use of 3D printers in various institutions, especially in orthognathic surgeries. In this study, we report a safe and inexpensive method of performing a high Le Fort I osteotomy using a novel 3D device and piezosurgery, which prevent tooth root injury without disturbing the operation field for patients with a short midface and long tooth roots. Results A 17-year-old woman presented with facial asymmetry, mandibular protrusion, a short midface, and long tooth roots. We planned high Le Fort I osteotomy and bilateral sagittal split ramus osteotomy. Prevention of damage to the roots of the teeth and the infraorbital nerve and accurate determination of the posterior osteotomy line were crucial for clinical success. Le Fort I osteotomy using 3D devices has been reported previously but were particularly large in size for this case. Additionally, setting the fixing screw of the device was difficult, because of the risk of damage to the roots of the teeth. Therefore, a different surgical technique, other than the conventional Le Fort I osteotomy and 3D device, was required. The left and right parts of the 3D device were fabricated separately, to prevent any interference in the surgical field. Further, the 3D device was designed to accurately cover the bone surface from the piriform aperture to the infra-zygomatic crest with two fixation points (the anterior nasal spine and the piriform aperture), which ensured stabilization of the 3D device. The device is thin and does not interfere with the surgical field. Safe and accurate surgical performance is possible using this device and piezosurgery. The roots of the teeth and the infraorbital nerve were unharmed during the surgery. Conclusions This device is considerably smaller than conventional devices and is a simple, low-cost, and efficient method for performing accurate high Le Fort I osteotomy.